Psychometric evaluation of the exercise-related cognitive errors questionnaire among Chinese emerging adults - Guo, Mengyao; Kuang, Jin; Wang, Ting; Herold, Fabian; Taylor, Alyx; Ng, Jonathan Leo; Hossain, M. Mahbub; Kramer, Arthur F.; Schinke, Robert; Cheng, Zhihui; Zou, Liye (Frontiers in Psychology, 2025)
BackgroundCognitive errors involve negatively biased or distorted thinking patterns that can hinder effective decision-making. When such a phenomenon occurs in the exercise domain, this is referred to as exercise-related cognitive error. Such exercise-related cognitive errors are typically assessed via a questionnaire, but a validated instrument for the application in Chinese-speaking populations is lacking. Thus, this study aims to validate the Chinese version of the Exercise-related Cognitive Errors Questionnaire (E-CEQ-C) among Chinese emerging adults, a self-report measure to evaluate cognitive errors of context-relevant information related to exercise.MethodsFollowing a forward-backward translation of the E-CEQ (N = 24 items), the E-CEQ-C and the Chinese version of the Cognitive Distortions Questionnaire (CD-Quest-C) for gathering evidence of criterion-related validity were administered among a sample of Chinese emerging adults (N = 376, 29.0% male) through an online survey. After a two-week interval, 105 out of 376 participants attended a re-test of the E-CEQ-C. Item analysis, confirmatory factor analysis (CFA), internal consistency, test–retest reliability, and concurrent validity were analyzed.ResultsThe findings from the CFA support the 24-item informed six-factor structure among Chinese emerging adults (χ2 = 699.038, RMSEA = 0.073, CFI = 0.919, TLI = 0.904, and SRMR = 0.055). Cronbach’s α of the six dimensions of the E-CEQ-C were all above 0.7. The test–retest reliability coefficients of each subscale and total scale were acceptable, ranging from 0.60 to 0.81. In accordance with the literature, we also observed positive associations between the six dimensions of E-CEQ-C and the constructs of the CD-Quest-C, which provided concurrent validity evidence for the E-CEQ-C.ConclusionThis study showed that E-CEQ-C is a psychometrically sound measure to assess exercise-related cognitive errors in Chinese-speaking populations.